Audio description for live performances and audience participation - Elena Di Giovanni (JoSTrans: The Journal of Specialised Translation)
Access services aiming to make live performances accessible to persons with sensory impairments are more and more a priority and a widespread practice. If providing accessibility to theatre plays, operas and other forms of live entertainment requires a deep knowledge −and detailed consideration− of the diverse needs of these segments of the audience, they also open up avenues for audience expansion. Relying on a two-year experiment in making opera accessible for people with visual impairments, and on the feedback they provided before, during and after accessible performances (in 2015 and 2016), this article reflects on audience participation as a tool for empowerment, increased awareness, sharing, universality. It offers a detailed discussion of the methodology and results obtained from observation protocols, questionnaires and interviews with accessibility providers and receivers. With a theoretical framework informed by audiovisual translation studies, reception and audience studies, the article also focuses on the positive, reversed trend whereby accessibility for special audiences becomes an asset for all. It concludes with overall comments regarding the findings of the experiment.